2009
DOI: 10.1177/0011000009338950
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attachment, Culturally Adjusted Attachment, and Interpersonal Difficulties of Taiwanese Adults

Abstract: This study examines the applicability of Western adult attachment perspectives to interpersonal difficulties experienced by individuals with indigenous Chinese cultural backgrounds. a total of 275 Taiwanese university students completed self-report surveys of adult attachment, ideal attachment, and interpersonal problems. Culturally adjusted attachment scores were generated by regressing self-report attachment on ideal attachment to control for cultural difference. Findings from path analyses indicated that cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…Theoretically, higher attachment anxiety is often associated with greater needs to seek external approval and higher tendencies to use hypervigilant coping strategies (Brennan et al, ). The indirect effect of attachment anxiety on somatic concerns through both higher levels of acquisition of mainstream cultural values and higher levels of endorsement of traditional cultural values found in this study may be conceptually explained by the fact that the high degree of attachment insecurity may have prompted individuals to deliberatively emphasize their indigenous cultural values when adjusting to a different culture yet at the same time overcompensate by assimilating themselves to more closely match the dominant culture (Wang & Scalise, ). From the attachment perspective, these strategies may be related to the needs of approval seeking and reassurance gathering (Brennan et al, )—instead of healthy, voluntary adaptation and integration—which then leads to greater levels of discrimination and psychological distress.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Theoretically, higher attachment anxiety is often associated with greater needs to seek external approval and higher tendencies to use hypervigilant coping strategies (Brennan et al, ). The indirect effect of attachment anxiety on somatic concerns through both higher levels of acquisition of mainstream cultural values and higher levels of endorsement of traditional cultural values found in this study may be conceptually explained by the fact that the high degree of attachment insecurity may have prompted individuals to deliberatively emphasize their indigenous cultural values when adjusting to a different culture yet at the same time overcompensate by assimilating themselves to more closely match the dominant culture (Wang & Scalise, ). From the attachment perspective, these strategies may be related to the needs of approval seeking and reassurance gathering (Brennan et al, )—instead of healthy, voluntary adaptation and integration—which then leads to greater levels of discrimination and psychological distress.…”
Section: Discussionmentioning
confidence: 86%
“…Attachment avoidance aligns more closely with the mistrust of others, or a negative internal working model of others, and excessive needs to be self‐reliant. Adult attachment anxiety and avoidance have each been found to relate positively to psychological distress (Wang & Scalise, ) and somatic concerns (Waldinger, Schulz, Barsky, & Ahern, ). Because most adult attachment studies rely on White, middle‐class samples, more research is needed to examine the application of attachment theory with Latino/Hispanic populations (Wang & Scalise, ).…”
Section: Acculturation and Adult Attachmentmentioning
confidence: 99%
“…Thus, Western‐based attachment constructs and self‐report instruments might not be immediately applicable to Asian populations without considering how their cultural beliefs and norms might bias Western‐based self‐report scores and responses. Previous studies (e.g., Wang & Mallinckrodt, ; Wang & Scalise, ) on cultural comparison (using Chinese‐version attachment scales adapted from Western‐based measures in Taiwanese participants) have evidenced that Taiwanese adults with indigenous Chinese cultural backgrounds reveal higher levels of attachment anxiety (for men) and attachment avoidance (for females) than Western adults. These authors suggested that future studies might adopt “culturally adjusted” attachment scores to explore variables of interest (for detailed protocol of operating culturally adjusted attachment scores, refer to Wang & Scalise's () study).…”
Section: Discussionmentioning
confidence: 99%
“…Our contextual attachment scales in Traditional‐Chinese were developed and validated in a sample of Taiwanese youth. However, cross‐cultural attachment researchers (e.g., Rothbaum, Weisz, Pott, Miyake, & Morelli, ; Takahashi, ; Wang & Mallinckrodt, ; Wang & Scalise, ) have questioned whether the fundamental concepts and tenets of attachment theory, rooted in Western ideals (e.g., emphasizing unique personal characteristics or considering self and others as separate units), might be contrary to the nature of traditional Chinese culture. Thus, Western‐based attachment constructs and self‐report instruments might not be immediately applicable to Asian populations without considering how their cultural beliefs and norms might bias Western‐based self‐report scores and responses.…”
Section: Discussionmentioning
confidence: 99%
“…With closer connection or correlation to this dissertation study, studied adult relationship satisfaction, depressive moods, and attachment styles . Although the impact of insecure attachment and depressive moods on relationship quality is well established for Caucasian American college students, research has been applied to the majority of Caucasian American college students but has not focused on the applicability of this theory to ethnic minority and international students in the United States (Wang & Ratanasiripong, 2010;Wang & Scalise, 2010).…”
Section: Theoretical Bases Of Romantic Relationshipsmentioning
confidence: 99%